Assessment of correlation of fasting blood glucose, Hb1Ac and serum Lipid Level in Type II Diabetes patients: A clinical study - Verma, Manohar Lal; Verma, Dr. Vidhi; Mishra, Pankaj Kr; Zaidi, Syed Hasan Nawaj (International Journal of Psychosocial Rehabilitation, 2020)
Diabetes is one of the debilitating pathology affecting a significant proportion of world’s population. The pathogenesis of dyslipidemia in diabetic patients is multifactorial. Major pathway is due to reduction in lipoprotein lipase activity because of insulin deficiency. Hence; the present study was undertaken for assessing correlation between fasting blood glucose, Hb1Ac and serum Lipid Level in Type II Diabetes patients.A total of 200 patients with confirmed diagnosis of type II diabetes mellitus were enrolled in the present study. Complete demographic and clinical data of all the patients was obtained. Patients were called in the morning time and fasting blood samples were obtained and were sent to central laboratory for assessment of fasting blood sugar (FBS) and glycosylated haemoglobin (HbA1C) levels. All the assessment was done using auto-analyser. Plasma lipoproteins were assessed through liberman-Buchard reaction. All the results were recorded in Microsoft excel sheet and were analysed using SPSS software. Mean age of the patients was found to be 53.7 years. While analysing statistically, it was observed that HbA1c levels significantly correlated with FBS levels and serum lipid profile in diabetic patients. In type II diabetic patients, HbA1c is significantly correlated with serum lipid profile. HbA1c levels can be used as a predictor of dyslipidemia in diabetic patients.